Peran Manajemen Strategis Dalam Meningkatkan Daya Saing Perusahaan Dalam Era Digital - Fokaaya, Saman (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to describe the role of strategic management in enhancing business competitiveness in the digital era, particularly among MSMEs in Kepulauan Sula Regency, North Maluku. The research employed a descriptive qualitative method with data collected through in-depth interviews, observation, and documentation. The findings indicate that businesses applying strategic management principles consistently tend to be more adaptive to digital transformations and are able to access broader markets. Key success factors include business vision, the ability to seize digital market opportunities, and support from local policies and communities. This research reinforces the significance of strategic management in navigating digital business dynamics, especially in island regions with limited infrastructure. The results are expected to serve as a reference for policymakers and entrepreneurs in designing locally grounded strategies.